Molecular epidemiology, genetic diversity, and vaccine availability of viral acute gastroenteritis in the middle East and North Africa (MENA) region. Issue 11 (November 2022) - Elbashir, Israa; Aldoos, Noor F.; Mathew, Shilu; Al Thani, Asmaa A.; Emara, Mohamed M.; Yassine, Hadi M.
Abstract: Acute gastroenteritis is the cause of considerable mortality and morbidity worldwide, particularly among children under five years in underdeveloped countries. Most acute gastroenteritis (AGE) cases are attributed to viral etiologies, including rotavirus, norovirus, adenovirus, astrovirus, and sapovirus. This paper aimed to determine the prevalence rate of different viral etiologies of AGE in the Middle East and North Africa (MENA) region. Moreover, this paper explored rotavirus phylogenetic relatedness, compared VP7 and VP4 antigenic regions of rotavirus with vaccine strains, and explored the availability of vaccines in the MENA region. The literature search identified 160 studies from 18 countries from 1980 to 2019. The overall prevalence of rotavirus, norovirus, adenovirus, astrovirus, and sapovirus were 29.8 %, 13.9 %, 6.3 %, 3.5 %, and 3.2 % of tested samples, respectively. The most common rotavirus genotype combinations in the MENA region were G1P[8], G9P[9], and G2P[4], whereas GII.4 was the predominant norovirus genotype all of which were reported in almost all the studies with genotyping data. The comparison of VP7 and VP4 between circulating rotavirus in the MENA region and vaccine strains has revealed discrete divergent regions, including the neutralizing epitopes. Rotavirus vaccine was introduced to most of the countries of the MENA region; however, only a few studies have assessed the effectiveness of vaccine introduction. This paper provides a comprehensive update on the prevalence of the different viral agents of AGE in the MENA region.